Comunicarea științifică în mediul online. In: Patrimoniul cultural de ieri – implicaţii în dezvoltarea societăţii durabile de mâine [Articol] - Eni, Mihaela (Academia de Ştiinţe a Moldovei, 2022)
In the context of the continuous development of society, in all its spheres of activity, communication remains the essential element in its evolution. Communication is a complex process, approached by specialists from various perspectives, because it is an existential process. Depending on the field of research, communication is studied on various dimensions. Scientific communication is of particular interest due to the accelerated development of science which later leads to the development of society. At national and international level, researchers meet to discuss the subject of scientific communication in the context of Open Access to Scientific Information. The way of organizing scientific events, their role, but also the characteristics of scientific communication in the online environment lately is a current research topic.
Scientific Communication in Online Environment
Keywords: sociologia culturii; comunicarea științifică; scientific communication; COVID-19; electronic platform; open access to information